Translation of Humor in Fansub and Official Subtitles in Hotel Transylvania 2 - Liu , Jiafei; Amirdabbaghian, Amin (Journal of Digital Sociohumanities, 2025)
Translating humor is a complex process that demands consideration of the target audience in terms of cultural background, language constraints, and cultural diversity. This study aims to systematically analyze and compare the translation strategies of fan and official subtitles in conveying humor in Hotel Transylvania 2 based on Pedersen’s (2005) translation strategy model. In addition, Nababan’s (2012) translation quality assessment model is used to explore and evaluate the impact of various translation strategies on the accuracy of both subtitles in the film. Humorous utterances from the English fantasy comedy Hotel Transylvania 2 screened on Netflix (Chinese official subtitles) as well as the fansub translated version from publicly available subtitle-sharing sites, are used as data in this study. Through qualitative analysis, this study evaluates the humor translation strategies and their accuracy level across Chinese and English languages and cultures. The findings demonstrate that certain strategies are widely used in both subtitles, some leading to a higher degree of inaccuracy in translations. These findings provide some implications for improving the accuracy and quality of humor translation in both official subtitles and fansubs of Hotel Transylvania 2.